Physiochemical Analysis of Community Water Supply in Kathmandu Valley - Shah, Dinesh (Journal of Innovations in Engineering Education, 2019)
This study was carried out to assess groundwater quality of the Kathmandu Valley, Nepal, because Safe drinking water is a basic need of all humans and to protect the human health, community water suppl y must be reliable, adequate and readily accessible to all segments of the consumers. For this the groundwater samples from eight different regions of the valley were collected during months of Jun-Jul in the year 2018. Th ese collected groundwater samples were analyzed various physio-chemical parameters such as temperature, colour, turbidity, pH, electric conductivity (EC), total alkalinity, phenolphthalein alkalinity, total hardness, iron, chloride,Nitrate and total ammonia using the procedure outlined in the standard methods. Results showed that the water quality status was found to vary from place to place. High levels of turbidity, total alkalinity, total hardness, iron and total ammonia were found in the groundwater of many sites. The results were compared with WHO water quality guideline and National Drinking Water Quality Standard (NDWQS) of Nepal.